Research progress on postharvest preservation of Chinese bayberry fruit - YANG Han; LI Xue; WANG Liqin; ZHANG He; KANG Chen; SUN Cui; CAO Jinping (浙江大学学报. 农业与生命科学版)
Chinese bayberry is a characteristic and native fruit of China, which is popular for its unique flavor and juicy taste. However, Chinese bayberry fruit has a short harvesting period and poor storability, thus is highly depending on the postharvest preservation and transportation technologies. There are numerous studies on the postharvest preservation and transportation of Chinese bayberry fruit. Based on these, this paper reviewed the research progress on postharvest quality change, disease and pest occurrence, storage and logistics technologies of Chinese bayberry fruit. After combing and looking forward to some researching key points, it is concluded that the reasons for the poor harvesting of Chinese bayberry fruit are diverse and complex, and the importance of forming a comprehensive technical system from many aspects is put forward. This paper provides some theoretical references for the research and application of postharvest preservation technologies of Chinese bayberry fruit.